Loss of protozoan and metazoan intestinal symbiont biodiversity in wild primates living in unprotected forests - Barelli, Claudia; Pafčo, Barbora; Manica, Mattia; Rovero, Francesco; Rosà, Roberto; Modrý, David; Hauffe, Heidi C (Scientific reports, 2020)
In light of the current biodiversity crisis, investigating the human impact on non-human primate gut biology is important to understanding the ecological significance of gut community dynamics across changing habitats and its role in conservation. Using traditional coproscopic parasitological techniques, we compared the gastrointestinal protozoan and metazoan symbiont richness of two primates: the Udzungwa red colobus (Procolobus gordonorum) and the yellow baboon (Papio cynocephalus). These species live sympatrically in both protected and unprotected forests within the Udzungwa Mountains of Tanzania with distinct ecological adaptations and diets. Our results showed that terrestrial and omnivorous yellow baboons had 2 (95% CI 1.47-2.73) and 3.78 (2.62-5.46) times higher gut symbiont richness (both including and excluding rare protozoans) compared to the arboreal and leaf-eating Udzungwa red colobus in unprotected and protected forest, respectively. We also found a consistent depletion of symbiont richness in red colobus living in the unprotected forest fragment compared to the continuous protected forests [the latter having 1.97 times (95% CI 1.33-2.92) higher richness], but not in yellow baboons. Richness reduction was particularly evident in the Udzungwa red colobus monkeys, confirming the pattern we reported previously for gut bacterial communities. This study demonstrates the impact of human activities even on the microbiodiversity of the intestinal tract of this species. Against the background of rapid global change and habitat degradation, and given the health benefits of intact gut communities, the decrease in natural gut symbionts reported here is worrying. Further study of these communities should form an essential part of the conservation framework.
Keywords: Animals; Forests; Intestines; biodiverzita; feces; Feces; Amoebida; Tanzania; lesy; druhová specificita; Colobus; Species Specificity; Symbiosis; Human Activities; Tanzanie; cizopasní červi; Trichostomatida; dieta; střeva; Diet; Papio; Helminths; Biodiversity; ekosystém; Ecosystem; lidské činnosti; symbióza; zvířata